Functional Activity of Antibodies Directed towards Flagellin Proteins of Non-Typhoidal Salmonella. - Girish Ramachandran (PLoS ONE, 2016)
Non-typhoidal Salmonella (NTS) serovars Typhimurium and Enteritidis are major causes of invasive bacterial infections in children under 5 years old in sub-Saharan Africa, with case fatality rates of ~20%. There are no licensed NTS vaccines for humans. Vaccines that induce antibodies against a Salmonella Typhi surface antigen, Vi polysaccharide, significantly protect humans against typhoid fever, establishing that immune responses to Salmonella surface antigens can be protective. Flagella proteins, abundant surface antigens in Salmonella serovars that cause human disease, are also powerful immunogens, but the functional capacity of elicited anti-flagellar antibodies and their role in facilitating bacterial clearance has been unclear. We examined the ability of anti-flagellar antibodies to mediate microbial killing by immune system components in-vitro and assessed their role in protecting mice against invasive Salmonella infection. Polyclonal (hyperimmune sera) and monoclonal antibodies raised against phase 1 flagellin proteins of S. Enteritidis and S. Typhimurium facilitated bacterial uptake and killing of the homologous serovar pathogen by phagocytes. Polyclonal anti-flagellar antibodies accompanied by complement also achieved direct bacterial killing. Serum bactericidal activity was restricted to Salmonella serovars expressing the same flagellin used as immunogen. Notably, individual anti-flagellin monoclonal antibodies with complement were not bactericidal, but this biological activity was restored when different monoclonal anti-flagellin antibodies were combined. Passive transfer immunization with a monoclonal IgG antibody specific for phase 1 flagellin from S. Typhimurium protected mice against lethal challenge with a representative African invasive S. Typhimurium strain. These findings have relevance for the use of flagellin proteins in NTS vaccines, and confirm the role of anti-flagellin antibodies as mediators of protective immunity.